2002
DOI: 10.3390/70700540
|View full text |Cite
|
Sign up to set email alerts
|

Michael Reactions of Arylidenesulfonylacetonitriles. A New Route to Polyfunctional Benzo[a]quinolizines

Abstract: Arylidenesulfonylacetonitriles react in acetonitrile with 1-methylisoquinoline and isoquinolin-1-yl-acetonitrile in the presence of piperidine to give benzo[a]quinolizines 6,9 and 7,10, respectively. The structures of the products were established on the basis of elemental and spectral analyses and their chemical reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[24][25][26][27][28][29] In conjunction with this work we report here the synthesis of the starting 2-chloro-3-formyl-9,10-dimethoxy-4-oxo-6,7dihydro-4H-pyrido[2,1-a]isoquinoline-1-carbonitrile (3) (Scheme 1). Treatment of 1-cyanomethylisoquinoline 1 with diethyl malonate in nitrobenzene and refluxed for 30 min gave 2-hydroxy-9,10dimethoxy-4-oxo-6,7-dihydro-4H-pyrido[2,1-a]isoquinoline-1-carbonitrile (2) in 92% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29] In conjunction with this work we report here the synthesis of the starting 2-chloro-3-formyl-9,10-dimethoxy-4-oxo-6,7dihydro-4H-pyrido[2,1-a]isoquinoline-1-carbonitrile (3) (Scheme 1). Treatment of 1-cyanomethylisoquinoline 1 with diethyl malonate in nitrobenzene and refluxed for 30 min gave 2-hydroxy-9,10dimethoxy-4-oxo-6,7-dihydro-4H-pyrido[2,1-a]isoquinoline-1-carbonitrile (2) in 92% yield.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Recently, we have been involved in the synthesis and chemistry of several fused isoqinoline derivatives. [18][19][20][21][22][23][24][25][26][27][28][29] In the present paper, we introduce a new and general route to pyrido[2,1-a]isoquinoline containing many reactive sites. The aim of this study, on one hand is to prepare a novel tetracyclic compounds starting from readily obtainable materials in good yields and on the other hand, to prepare compounds that might have pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%
“…High yielding syntheses of polyfunctional benzo[a]quinolizines are well-documented [264]. Abdallah et al [265] reported a new and general one-step route affording polyfunctional substituted benzo[a] quinolizines in good yield from readily available inexpensive starting materials using isoquinoline derivatives. Thus, treatment of 1-methyl isoquinoline 334 with arylidenesulfonylacetonitriles 333 in boiling acetonitrile in the presence of an equimolar amount of piperidine leads, in each case, to the formation of only one product 337 and 338, as indicated by TLC and 1H-NMR analysis.…”
Section: Scheme 111mentioning
confidence: 99%
“…Also, benzo[a]isoquinolines have been associated with a variety of interesting pharmacological properties, among which chemotherapeutic , neuroleptic , anticonvulsant , and anti‐inflammatory . Our research group for 15 years has been focusing on the synthesis of isoquinoline‐containing compounds, and a variety of chemically diverse structures with biological and antitumor activity were obtained . In addition, we have also been interested in the search of new compounds with antitumor properties.…”
Section: Introductionmentioning
confidence: 99%